High-aspect-ratio nanostructured surfaces as biological metamaterials - Higgins,S; Becce,M; Belessiotis,Richards A; Seong,H; Sero,J; Stevens,M (Advanced Materials, 2020)
Materials patterned with high-aspect-ratio nanostructures have features on similar lengthscales to cellular components. These surfaces are an extreme topography on the cellular leveland have become useful tools for perturbing and sensing the cellular environment. Motivationcomes from the ability of high-aspect-ratio nanostructures to deliver cargoes into cells andtissues, access the intracellular environment, and control cell behavior. These structuresdirectly perturb cells’ ability to sense and respond to external forces, influencing cell fate andenabling new mechanistic studies. Through careful design of their nanoscale structure, thesesystems act as biological metamaterials, eliciting unusual biological responses. Whilepredominantly used to interface eukaryotic cells, there is growing interest in non-animal andprokaryotic cell interfacing. Both experimental and theoretical studies have attempted todevelop a mechanistic understanding for the observed behaviors, predominantly focusing onthe cell – nanostructure interface. Here, we consider how high-aspect-ratio nanostructuredsurfaces are used to both stimulate and sense biological systems and discuss remainingresearch questions.